Commodity and consumer qualities of fruits of plum cultivars from the RRIFCB (VNIISPK) gene pool - A. A. Gulyaeva; T. N. Berlova; E. V. Bezlepkina; A. A. Galkova; I. N. Efremov (Овощи России, 2020)
Relevance. One of the most important directions in the breeding and variety study of fruits, in particular domestic plum European, is the breeding of cultivars with high commercial and consumer qualities of fruits. In this regard, the assessment of some commercial and consumer qualities of fruits in plum cultivars of the RRIFCB gene pool was of great practical and scientific interest. Material and methods. As objects of research, we used 8 plum cultivars of the RRIFCB gene pool and a control cultivar of the RRIFCB breeding Bolkhovchanka. The studies were carried out on the basis of the laboratory of breeding and variety study of stone fruit crops of RRIFCB in 2015-2019. Determination of color, shape, average weight, taste, size of fruit, size and shape of the stone, density of pulp, separation and length of the stalk, color of the juice were carried out in accordance with the "Program and methodology for the variety study of stone fruit crops" and "Pomology". Results. Most of the studied plum cultivars from the gene pool of the Russian Research Institute for Fruit Crops Breeding have valuable commercial and consumer qualities of fruits, which will allow them to be used in further breeding for this trait. Cultivars Californiyskaya krupnaya, Zarechnaya rannyaya, Volgogradskaya can be recommended for further use in breeding as sources of high fruit mass. Cultivars Californiyskaya krupnaya and Bolkhovchanka can be recommended for further use in breeding as sources of high pulp content in fruits and fruit sizes. On the basis of the tasting assessment of the fresh fruits, the fruits of the cultivar Volgogradskaya stood out positively.